TI_GERICHTE 14.2011.100 vom 19. August 2011 , Rigetto provvisorio. Nessun dubbio in merito all'identità della creditrice - TI Tribunale d'appello (2011)
Rigetto provvisorio. Nessun dubbio in merito all'identità della creditrice